Pengembangan Model Daya Saing UMKM Batik Melalui ECS - Dewanti, Retno; Melati, Ina; Simbolon, Freddy (Binus Business Review, 2013)
SMEC has high durability against any unpleasant economic conditions. Moreover, SMALL MEDIUM ENTERPRISES of batik has had the ability to produce export and derived foreign exchange for the country. It is important to continue to do the construction and development of batik industry competitiveness in order to compete in this era of free trade. The purpose of this research is to find a development Model as an integrated system capability of integrating Indonesian batik business, which is Â supported by the existing infrastructure so that it is capable of being one of the pre-eminent business typical batik Indonesia which has been recognized as one of the world heritage of Indonesian as a nation. Methods the study was a qualitative Method to find the organization model and hybrid formulation of e community system to support collaboration among organizations. This research has enabled independent business group supported a Hybrid organization building strength together in the era of globalization based on Electronic Community System that is driven by each component in the Hybrid Organization.